Jumping to conclusions, general intelligence, and psychosis liability: findings from the multi-centre EU-GEI case-control study. Issue 4 (24th March 2021) - Tripoli, Giada; Quattrone, Diego; Ferraro, Laura; Gayer-Anderson, Charlotte; Rodriguez, Victoria; La Cascia, Caterina; La Barbera, Daniele; Sartorio, Crocettarachele; Seminerio, Fabio; Tarricone, Ilaria; Berardi, Domenico; Szöke, Andrei; et al.
Abstract: Background: The 'jumping to conclusions' (JTC) bias is associated with both psychosis and general cognition but their relationship is unclear. In this study, we set out to clarify the relationship between the JTC bias, IQ, psychosis and polygenic liability to schizophrenia and IQ. Methods: A total of 817 first episode psychosis patients and 1294 population-based controls completed assessments of general intelligence (IQ), and JTC, and provided blood or saliva samples from which we extracted DNA and computed polygenic risk scores for IQ and schizophrenia. Results: The estimated proportion of the total effect of case/control differences on JTC mediated by IQ was 79%. Schizophrenia polygenic risk score was non-significantly associated with a higher number of beads drawn ( B = 0.47, 95% CI −0.21 to 1.16, p = 0.17); whereas IQ PRS ( B = 0.51, 95% CI 0.25–0.76, p < 0.001) significantly predicted the number of beads drawn, and was thus associated with reduced JTC bias. The JTC was more strongly associated with the higher level of psychotic-like experiences (PLEs) in controls, including after controlling for IQ ( B = −1.7, 95% CI −2.8 to −0.5, p = 0.006), but did not relate to delusions in patients. Conclusions: Our findings suggest that the JTC reasoning bias in psychosis might not be a specific cognitive deficit but rather a manifestation or consequence, of general cognitive impairment. Whereas, in the general population, the JTC bias is related to PLEs, independent of IQ. The work has the potential to inform interventions targeting cognitive biases in early psychosis.